Cranial Electrotherapy Stimulation and Influence of the Hart Rate Variability - Līcis, Renārs; Molotanovs, Andris; Žīdens, Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Before the competition are very important to be in optimal functional position. We were using CES to perform the functional position of optimization. Also we use CES to prescribe autonomic nervous system, analyzing the 11 handball players. After using cranial electrotherapy stimulation, we can see fundamental changes of heart rate, statistical analysis and spectral analysis indicator. After using electro cranial therapy stimulation, in one hour maximize autonomic nervous system tonus and parasympathetic activity. Using electro cranial stimulation are very effective before competition when sportsman feel`s tired, lowspirited, disquiet or upset.